2011
DOI: 10.1124/jpet.111.183871
|View full text |Cite
|
Sign up to set email alerts
|

Direct Evidence for the Formation of Diastereoisomeric Benzylpenicilloyl Haptens from Benzylpenicillin and Benzylpenicillenic Acid in Patients

Abstract: Covalent binding to proteins to form neoantigens is thought to be central to the pathogenesis of penicillin hypersensitivity reactions. We have undertaken detailed mass spectrometric studies to define the mechanism and protein chemistry of hapten formation from benzylpenicillin (BP) and its rearrangement product, benzylpenicillenic acid (PA). Mass spectrometric analysis of human serum albumin exposed to BP and PA in vitro revealed that at low concentrations (drug protein molar ratio 0.001:1) and during short t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
99
0
3

Year Published

2012
2012
2023
2023

Publication Types

Select...
5
3

Relationship

2
6

Authors

Journals

citations
Cited by 81 publications
(104 citation statements)
references
References 28 publications
2
99
0
3
Order By: Relevance
“…␤-Lactam antibiotics are known to be targeted by specific Lys residues on protein (Levine and Ovary, 1961;Batchelor et al, 1965;Meng et al, 2011). Nucleophilic attack leads to ring opening, binding of the penicilloyl group, and ultimately formation of a stable adduct.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…␤-Lactam antibiotics are known to be targeted by specific Lys residues on protein (Levine and Ovary, 1961;Batchelor et al, 1965;Meng et al, 2011). Nucleophilic attack leads to ring opening, binding of the penicilloyl group, and ultimately formation of a stable adduct.…”
Section: Discussionmentioning
confidence: 99%
“…To identify the key piperacillin-modified lysine residues in albumin involved in the stimulation of T-cell clones, we used our recently described mass spectrometry methods (Meng et al, 2011;Whitaker et al, 2011b). Before mass spectrometry, all samples were incubated with dithiothreitol (10 mM) at room temperature for 15 min and iodoacetamide (166 mM) for another 15 min at room temperature before again being subjected to methanol precipitation.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…The haptenation process occurs through the nucleophilic opening of the β-lactam ring by the attack of free amino groups in proteins, particularly modelling molecular studies found that the most reactive residues towards to amoxicillin is the Lysine, favouring the amoxicilloyl-protein adduct formation, which is able to elicit an immune response [109][110][111][112].…”
Section: Immuno-allergic Potentialmentioning
confidence: 99%
“…9,10 Such a process may result in upregulation of the antigenicity of the carriers, or both of the carriers and haptens. A number of haptens have been recognized relating the pathogenesis of allergic diseases including some plant derivatives (such as urushiol 11 ), some drugs (such as penicillin 12 ) and chemicals (such as trinitrobenzene sulfonic acid 13 ). The role of hapten in the animal model of allergic dermatitis has been well recognized, 14 in which haptens fulfill the role of adjuvants.…”
Section: Introductionmentioning
confidence: 99%